EVALUATION OF KIDNEY DRAINAGE OF THE IN ACUTE OBSTRUCTIVE PYELONEPHRITIS - S. V. Shkodkin; Y. B. Idashkin; V. V. Fentisov; A. V. Lubushkin; A. A. Nevskyi (Вестник урологии, 2018)
Introduction. Currently, there are no generally recognized indications for the choice of methods of drainage of the upper urinary tract in obstructive uropathy. Both external and internal drainage involve a number of shortcomings affecting the quality of life of the patient.Purpose of research. To evaluate the effectiveness of internal stenting (IC) and puncture nephrostomy (PN) as a method of temporary drainage of the upper urinary tract in acute obstructive pyelonephritis.Materials and methods. During 2012-2017 we observed 156 patients of both sexes aged from 25 to 74 years with the clinic of acute obstructive pyelonephritis against the background of urolithiasis. To restore the passage of urine is made stenting jj-stent or puncture nephrostomy. Materials and methods. During 2012-2017, we observed 156 patients of both sexes aged 25 to 74 years with a clinical picture of acute obstructive pyelonephritis on the background of urolithiasis. To restore the passage of urine is made stenting jj-stent or puncture nephrostomy.Results. Clinically, fever in the PN group was stopped for 1.8±0.5 days, and in the IC group this indicator was 5.5±2.8. In the IC group, 18 (58.1%) patients complained of irritative symptoms of varying severity, and in 9 (29.0%) patients pain syndrome in the lower back associated with myction was noted. No similar complications were observed in the PN group. The inability to install and inadequate function of the IC group in 45.5% of cases required conversion in the PN group. The need for revision of the kidney after the PN group was noted in 0.8% of cases (p<0.01).Conclusion. Subject to adequate techniques of puncture of the kidney and the combined (ultrasonic and radiographic) control the conduct of puncture nephrostomy is a safe method of drainage of the kidney in acute obstructive pyelonephritis, ensuring laying of drainage is of adequate diameter that allows you to get the best results for the relief of pyelonephritis in comparison with the inner stent.